2011
DOI: 10.1007/s11104-011-0901-0
|View full text |Cite
|
Sign up to set email alerts
|

Availability of sparingly soluble phosphorus sources to cotton (Gossypium hirsutum L.), wheat (Triticum aestivum L.) and white lupin (Lupinus albus L.) with different forms of nitrogen as evaluated by a 32P isotopic dilution technique

Abstract: Background & Aims Previous studies revealed that cotton plants grown on soils with low available-P were accessing significant non-fertilizer P sources. This suggests that cotton can access stable-P pools from soil. This study examined cotton's ability to utilize sparingly soluble P sources in comparison with wheat and white lupin. Methods Plants were grown for 45 days in a Vertosol supplied with AlPO 4 and hydroxyapatite, and NH 4 -N or NO 3 -N. A 32 P dilution technique was used to determine the availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…-June, 2016 that developing cultivars that have a greater capacity to grow in soils with low P availability could offer an alternative to P fertilizers (Zhang et al, 2012). Research on phosphorus efficiency has been conducted in a variety of crop species, including soybean (Wang, Guppy, Watson, Sale, & Tang, 2011), corn (Fageria & Baligar, 1997), common bean (Liao et al, 2004), rice (Fageria, Baeta, & Alexandre, 2011), and wheat (Ma et al, 2011). However, very little is known about cotton P use efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…-June, 2016 that developing cultivars that have a greater capacity to grow in soils with low P availability could offer an alternative to P fertilizers (Zhang et al, 2012). Research on phosphorus efficiency has been conducted in a variety of crop species, including soybean (Wang, Guppy, Watson, Sale, & Tang, 2011), corn (Fageria & Baligar, 1997), common bean (Liao et al, 2004), rice (Fageria, Baeta, & Alexandre, 2011), and wheat (Ma et al, 2011). However, very little is known about cotton P use efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of published work has emphasized the high adaptability of some legume species, including white lupine, to low-P environments (Braum and Helmke, 1995;Uhde-Stone et al, 2003;Schulze et al, 2006;Tomasi et al, 2008), in this study white lupine and the other legume species displayed only modest results in the utilization of P from the soil. Indeed, other authors have experienced some inability to demonstrate the efficiency of white lupine in P acquisition from sparingly soluble aluminium phosphate (AlPO 4 ) (Wang et al, 2010(Wang et al, , 2011. Probably the mobilization of P depends on what the major P pools in the soil are.…”
Section: Discussionmentioning
confidence: 99%
“…The low availability of P in most soils and the increasing scarcity of phosphate rocks is causing the scientific community to seek alternatives such as the use of the indigenous soil P pools more efficiently. The plants efficient in utilizing sparingly soluble soil P have been receiving great attention from the scientific community, particularly in the last two decades (Braum and Helmke, 1995;Veneklaas et al, 2003;Watt and Evans, 2003;Tomasi et al, 2008;Wang et al, 2010Wang et al, , 2011Sepehr et al, 2012). This study aims to evaluate the ability of various legume species to increase soil P availability when they are grown as cover crops in traditional olive groves.…”
mentioning
confidence: 99%
“…In this case, it was assumed that 40% of the total 130 μg P seed −1 was translocated to the shoots, based on this amount being measured in the study by Wang et al (2011), who used a sand-growing medium with P-free nutrient additions to determine the translocation of seed-P to the shoots in wheat plants. Pypers et al (2006) showed that the transfer of P from the seed to the shoots of maize and cowpea varied from 40% to 90% for low-P and high-P soils, respectively.…”
Section: Calculationsmentioning
confidence: 99%